Fly slab Concrete Application on The High-Rise Building Structure: Review of Material Use Efficiency - Rois, Amin; Pangestuti, Endah Kanti (Semarang State University, 2020)
Abstract Innovations on the use of precast concrete are developing rapidly, one of them is a fly slab precast plate. Fly slab is a reinforced concrete mixture designed using high quality technology to produce concrete that is more effective, efficient and economical than conventional concrete. The concept is to reduce the mass of a precast concrete floor plate by making ribs on a concrete floor plate. By minimizing the volume of concrete in the tensile area of the floor plate while maintaining the mechanism of force transfer from concrete to reinforcement or on other contrary, it is expected to reduce the mass of the structure without reducing its strength. The objective of this research is to find out how much the efficiency of material requirements in planning earthquake resistant building structures using fly slab plates. The results of the analysis showed that the total weight reduction was 18.46% and the total concrete volume reduction was 26.53%. Reduction of structure vertical reaction was 30.78%.